Measuring the Quality of Palliative Care for Patients with End-Stage Liver Disease - Patel, Arpan (Dig Dis Sci, 2020)
BACKGROUND/AIMS: We examined the quality of palliative care received by patients with decompensated cirrhosis using an explicit set of palliative care quality indicators (QIs) for patients with end-stage liver disease (PC-ESLD). METHODS: We identified patients newly diagnosed with decompensated cirrhosis at a single veterans health center and followed up them for 2 years or until death. We piloted measurement of PC-ESLD QIs in all patients confirmed to have ESLD using a chart abstraction tool. RESULTS: Out of 167 patients identified using at least one sampling strategy, 62 were confirmed to meet ESLD criteria with chart abstraction. Ninety-eight percent of veterans in the cohort were male, mean age at diagnosis was 61 years, and 74% were White. The overall QI pass rate was 68% (64% for information care planning QIs and 76% for supportive care QIs). Patients receiving specialty palliative care consultation were more likely to receive information care planning QIs (67% vs. 37%, p = 0.02). The best performing sampling strategy had a sensitivity of 62% and specificity of 60%. CONCLUSION: Measuring the quality of palliative care for patients with ESLD is feasible in the veteran population. Our single-center data suggest that the quality of palliative care is inadequate in the veteran population with ESLD, though patients offered specialty palliative care consultation and those affected by homelessness, drug, and alcohol abuse may receive better care. Our combination of ICD-9 codes can be used to identify a cohort of patients with ESLD, though better sensitivity and specificity may be needed.